Superparamagnetic nanoarchitectures for disease-specific biomarker detection. (13th November 2019) - Masud, Mostafa Kamal; Na, Jongbeom; Younus, Muhammad; Hossain, Md. Shahriar A.; Bando, Yoshio; Shiddiky, Muhammad J. A.; Yamauchi, Yusuke
Abstract : Synthesis, bio-functionalization, and multifunctional activities of superparamagnetic-nanostructures have been extensively reviewed with a particular emphasis on their uses in a range of disease-specific biomarker detection and associated challenges. Abstract : The detection of clinically relevant disease-specific biomolecules, including nucleic acids, circulating tumor cells, proteins, antibodies, and extracellular vesicles, has been indispensable to understand their functions in disease diagnosis and prognosis. Therefore, a biosensor for the robust, ultrasensitive, and selective detection of these low-abundant biomolecules in body fluids (blood, urine, and saliva) is emerging in current clinical research. In recent years, nanomaterials, especially superparamagnetic nanomaterials, have played essential roles in biosensing due to their intrinsic magnetic, electrochemical, and optical properties. However, engineered multicomponent magnetic nanoparticle-based current biosensors that offer the advantages of excellent stability in a complex biomatrix; easy and alterable biorecognition of ligands, antibodies, and receptor molecules; and unified point-of-care integration have yet to be achieved. This review introduces the recent advances in superparamagnetic nanostructures for electrochemical and optical biosensing for disease-specific biomarkers. This review emphasizes the synthesis, biofunctionalization, and intrinsic properties of nanomaterials essential for robust, ultrasensitive biosensing. With a particular emphasis on nanostructure-based electrochemical and optical detection of disease-specific biomarkers such as nucleic acids (DNA and RNA), proteins, autoantibodies, and cells, this review also chronicles the needs and challenges of nanoarchitecture-based detection. These summaries provide further insights for researchers to inspire their future work on the development of nanostructures for integrating into biosensing and devices for a broad field of applications in analytical sensing and in clinic.